Methods And Means Of Educating Youth In The Spirit Of National Values - Mavluda Musurmonova (Euro Asian Journal Publishing, 2024)
The article reflects on existing modern methods and means of educating students in the spirit of national values in educational institutions and makes recommendations
Keywords: Youth education; methods and means of education; educational process